2020
DOI: 10.1074/jbc.ra120.012882
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of core 2 O-glycans on synovial lubricin in osteoarthritis reduces galectin-3 mediated crosslinking

Abstract: The synovial fluid glycoprotein lubricin (also known as proteoglycan 4) is a mucin-type O-linked glycosylated biological lubricant implicated to be involved in osteoarthritis (OA) development. Lubricin’s ability to reduce friction is related to its glycosylation consisting of sialylated and unsialylated Tn-antigens, core-1 and core-2 structures. The glycans on lubricin have also been suggested to be involved in crosslinking and stabilization of the lubricating superficial layer of cartilage by mediating intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 70 publications
6
21
0
Order By: Relevance
“…Using ELISA on SF from 29 OA and 19 non-OA control we could infer that SF lubricin on our OA patient cohort contained significant more Tn antigens compared to T-antigens (Figure 6B). This showed that the oligosaccharides on OA lubricin are shorter than the controls, in line with previous publication(13).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Using ELISA on SF from 29 OA and 19 non-OA control we could infer that SF lubricin on our OA patient cohort contained significant more Tn antigens compared to T-antigens (Figure 6B). This showed that the oligosaccharides on OA lubricin are shorter than the controls, in line with previous publication(13).…”
Section: Resultssupporting
confidence: 93%
“…TNF-α as well as IL-6 have been shown to up-regulate Tn levels in gingival fibroblasts, probably by downregulation of the COSMC chaperon required for activation of the core-1 galactosyl transferase that allows O -linked glycans to be elongated. This latest example would provide a the type of truncation of the glycosylation profile consistent with what has been observed in on OA lubricin in this report and previous(13). MIP-1α is a chemokine with limited information about its association with OA.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations